Sequential rationality in continuous no-limit poker - Thomas W. L. Norman (Games, 2014)
Newman's (1959, Operations Research, 7, 557-560) solution for a variant of poker with continuous hand spaces and an unlimited bet size is modified to incorporate sequential rationality.
Keywords: 330; poker; mixed strategies; sequential rationality